Pengembangan soal matematika tipe PISA konten quantity menggunakan konteks kopi khas Jambi untuk siswa SMP - Lusiana; Pasaribu, Feri Tiona; Gustiningsi, Tria; Nusantara, Duano Sapta (IKIP Siliwangi, 2025)
The low mathematical literacy ability is the background of this study. The aim is to create PISA type mathematics questions with quantity content using the context of Jambi's specialty coffee that are valid, practical, and have a potential effect on mathematical literacy skills. The study method used is the design research model development studies, namely preliminary, prototyping with a series of formative evaluation stages including self-evaluation, expert review, one to one, small group, and field test and assessment phase. The study subjects were 29 students of class VIII SMP N 22 Jambi City. Data were obtained using walk through, tests, questionnaires and interviews. This study presents PISA type mathematics questions with quantity content, especially the topic of comparison. The context is personal, namely Jambi's specialty coffee. The questions produced are included in the reasoning level category. The questions produced are valid and easy qualitatively and have a potential effect on mathematical literacy skills. In addition, by linking mathematics questions to contexts known to students, such as Jambi coffee, it makes it easier for students to understand abstract mathematical concepts.